The contribution of person-organization fit to employee engagement - Ünal, Zeynep Merve (My University, 2013)
Bu araştırmanın temel amacı, birey-örgüt değer uyumunun çalışan tutkunluğuna katkısını incelemektir. Bağımsız değişken olan birey-örgüt uyumu kavramının bağımlı değişken olan çalışan tutkunluğu kavramı üzerinde açıklayıcılığa sahip olduğu öngörülmüştür. Birey-örgüt uyumu bireyin değerleri ile örgütünün değerleri arasındaki benzerlik derecesi olarak ele alınmıştır. Bağımlı değişken olan çalışan tutkunluğu kavramı da çalışmaya tutkunluk ve örgüte tutkunluk olarak iki boyutta incelenmiştir. Birey-örgüt uyumu ve çalışmaya tutkunluk örgütsel davranış yazınında pek çok kez incelenmiştir. Ancak birey-örgüt uyumu ve çalışan tutkunluğunun ilişkisini vurgulayan araştırma yazında bulunmamaktadır. Bu noktada, araştırmamız özgün bir nitelik taşımaktadır. Araştırmamızın örneklem grubunu farklı sektörlere ait çeşitli firma çalışanları oluşturmaktadır. 285 kişiye uyguladığımız araştırma ölçeğinin analizleri için istatistik kullanılmıştır. Uygulanan regresyon analizi sonucunda değer uyumunun hem çalışmaya tutkunluk hem de örgüte tutkunluk üzerinde anlamlı bir katkısının olduğu bulunmuştur. tsel Değer, Birey-örgüt Uyumu, Çalışan Tutkunluğu, Çalışmaya Tutkunluk, Örgüte Tutkunluk

The main purpose of our research is to investigate the relationship between person-organization value fit and employee engagement. We predict that, independent variable ‘‘person-organization fit’’ has a contribution on dependent variable ‘‘employee engagement’’. Person-organization fit was addressed as the degree of similarity between personal value and organizational value. Employee engagement was divided into two dimensions which are ‘‘work engagement’’ and ‘‘organizational engagement’’. In academic literature, person-organization fit and work engagement has been investigated concepts for a long time. However, there is no research which emphasizes the relationship between person-organization fit and employee engagement. At this point, our research has its own originality. The group of participants in this research are employees from different companies that belong to different sectors. Research scale was answered by 285 participants and statistical package program is used to test hypothesis and research questions. According to the results obtained through regression analysis, person-organization fit has a significant contribution on both of employee engagement concepts. Key words: Value, Organizational Value, Person-Organization Fit, Employee Engagement, Work Engagement, Organizational Engagement
Keywords: Örgütsel Davranış